文化心理劇：「景觀人，人觀景」用於變遷中的華人家庭關係議題 - 李御儂(Yunung Lee); 賴念華(Nien-Hwa Lai) (Chinese Journal of Guidance & Counseling, 2019)
This study aimed to investigate the group process and effects of a Chinese indigenous psychodramatic model titled, "Seeing from The Scenes; Seeing from The Person". This model was invented to address and resolve relational issues within families arising from the Western-Chinese bi-cultural phenomena/conflicts in contemporary Chinese societies. The bi-cultural phenomena refer to clients ‘struggles between pursuing individual independence and autonomy (modernity) and maintaining relational harmony (traditionality), resulting in their attempts to seek counseling and psychotherapy. Meanwhile, the bi-cultural conflicts emerge in the counseling process from clients' contradictory needs for self-disclosure and self-affirmation (individualismoriented) and simultaneously to save face for selves and others (collectivism-oriented). Inspired by the "cannon of creativity" in psychodramatic theory, researchers developed a ten-step working model based on psychodrama's unique perspectives on time and space. The ten steps inc